2009
DOI: 10.1016/j.bpj.2008.12.3957
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Insulin Filaments Induced by Reducing Disulfide Bonds Show a Different Morphology, Secondary Structure, and Cell Toxicity from Intact Insulin Amyloid Fibrils

Abstract: Amyloid fibrils are associated with more than 20 diseases, including Alzheimer's disease and type II diabetes. Insulin is a 51-residue polypeptide hormone, with its two polypeptide chains linked by one intrachain and two interchain disulfide bonds, and has long been known to self-assemble in vitro into amyloid fibrils. We demonstrate here that bovine insulin forms flexible filaments in the presence of a reducing agent, Tris (2-carboxyethyl) phosphine. The insulin filaments, possibly formed due to partial reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(159 citation statements)
references
References 44 publications
12
145
2
Order By: Relevance
“…conformation or non-toxic filaments with anti-parallel b-sheet character under reducing conditions (Zako, Sakono, Hashimoto, Ihara, & Maeda, 2009).…”
Section: Abbreviationsmentioning
confidence: 99%
“…conformation or non-toxic filaments with anti-parallel b-sheet character under reducing conditions (Zako, Sakono, Hashimoto, Ihara, & Maeda, 2009).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Several techniques have been employed to study fibril formation including circular dichroism (CD), 14,15 transmission electron microscopy (TEM), 16 atomic force microscopy (AFM), 17 X-ray diffraction 18 and others. [19][20][21] CD spectroscopy studies showed that insulin adopts -helical conformations that can convert to appreciably -pleated structures as a function of time.…”
mentioning
confidence: 99%
“…Conversion from a helical structure to a β-sheet structure has been reported for the pathogenic prion protein (Prusiner 1998) and amyloid beta peptide (Rauk 2008). Similar change in CD spectra is reported for fibril forming peptides such as insulin (Zako et al 2009) and Aβ peptide (Tomaselli et al 2006). Recently, Agno was reported to exist outside of the infected cell (Otlu et al 2014).…”
Section: Discussionmentioning
confidence: 66%